Community-Supported Learning: Practicums, Adult Education and Post-Secondary Institutions - Sumner, Jennifer (Alberta Journal of Educational Research, 2018)
Practicums are a form of adult education that moves the post-secondary institution beyond the classroom and into the community. As adult learning experiences, they are unparalleled, combining the resources of the academy with the opportunities of the wider world. This paper will explore the links between adult education and post-secondary institutions through the phenomenon of the practicum. Using a tripartite lens of social, experiential and workplace learning, it will examine a particular practicum course to understand how it enables communities of practice – ongoing processes of collective learning in a shared domain of human endeavour (Wenger, 2011). These communities of practice, in turn, foster what can be understood as community-supported learning, part of the foundation of ‘really useful knowledge’ that characterizes the broad and vital mission of adult education. Les stages sont une forme d’éducation des adultes qui sort l’apprentissage postsecondaire de la salle de classe et la situe dans la communauté. En tant qu’expériences d’apprentissage pour les adultes, ils sont inégalés, alliant les ressources d’une institution académique aux occasions du reste du monde. Cet article explorera les liens entre l’éducation des adultes et les institutions postsecondaires par le biais du phénomène des stages. S’appuyant sur la perspective tripartite de l’apprentissage social, expérientiel et en milieu de travail, l’article examinera un stage en particulier de sorte à comprendre comment il rend possible des communautés de pratique – des processus permanents d’apprentissage collectif dans une sphère partagée d’activité humaine (Wenger, 2011). Ces communautés de pratique, à leur tour, favorisent ce qu’on peut nommer l’apprentissage appuyé par la communauté, composante du fondement de « connaissances très utiles » qui caractérisent la mission élargie et vitale qu’est celle de l’éducation des adultes. Mots clés : stage, éducation des adultes, apprentissage appuyé par la communauté